Polynomials in Control Theory Parametrized by Their Roots - Baltazar Aguirre-Hernández; José Luis Cisneros-Molina; Martín-Eduardo Frías-Armenta (International Journal of Mathematics and Mathematical Sciences)
The aim of this paper is to introduce the space of roots to study the topological properties of the spaces of polynomials. Instead of identifying a monic complex polynomial with the vector of its coefficients, we identify it with the set of its roots. Viète's map gives a homeomorphism between the space of roots and the space of coefficients and it gives an explicit formula to relate both spaces. Using this viewpoint we establish that the space of monic (Schur or Hurwitz) aperiodic polynomials is contractible. Additionally we obtain a Boundary Theorem.